2005
DOI: 10.1097/01.prs.0000148372.75342.d9
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Treatment Enhances the Repair and Regeneration of Wounds in Mice Exposed to Hemibody ??-Irradiation

Abstract: Hemibody irradiation in multiple fractionated doses is frequently used for the treatment of various neoplastic disorders. It produces both acute and late effects on the skin and subcutaneous tissues that have profound implications in the healing of surgical wounds. Because of the crucial practical importance of hemibody radiation exposure associated with skin wounds, it is imperative to investigate the efficacy of cost-effective herbal products in the reconstruction of irradiated wounds. Therefore, the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 37 publications
11
88
0
2
Order By: Relevance
“…Whole body irradiation of mice to 6 Gy caused a significant retardation in wound contraction leading to an increase in the wound healing time significantly in mice. This is in conformation with earlier studies, where a similar effect has been reported [8,[12][13][14]16,47]. This may be due to several possible reasons including inhibition of inflammatory reactions, fibroblast and connective tissue proliferation, formation and maturation of granulation tissue after irradiation [4,9,48].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Whole body irradiation of mice to 6 Gy caused a significant retardation in wound contraction leading to an increase in the wound healing time significantly in mice. This is in conformation with earlier studies, where a similar effect has been reported [8,[12][13][14]16,47]. This may be due to several possible reasons including inhibition of inflammatory reactions, fibroblast and connective tissue proliferation, formation and maturation of granulation tissue after irradiation [4,9,48].…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, topical application of curcumin ointment has been reported to accelerate the healing of irradiated excision wound recently [60]. The ascorbic acid and curcumin have been reported to accelerate healing of wounds in mice exposed to whole body γ-radiation [12,14,61,62]. The extract of Nigella sativa has been also reported to enhance the healing of irradiated wound recently [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin also downregulates the expression of COX2, LOX, NOS, MMP-9, TNF-α, cell surface adhesion molecules, and cyclin D1 (Aggarwal et al, 2004) which are important players of inflammatory and anti-inflammatory responses. Curcumin pretreatment enhances the synthesis of collagen, hexosamine, DNA, nitrite, and histologic assessment of wound biopsy specimens showed improved collagen deposition and an increase in fibroblast and vascular densities suggesting that curcumin may be able to improve radiation-induced delay in wound repair (Jagetia and Rajanikant, 2005). The use of herbal products in the treatment of wound may be of wide acceptability, better tolerance and inexpensive.…”
Section: Issn: 2319-7706 Volume 6 Number 7 (2017) Pp 2263-2273mentioning
confidence: 99%